PEMBERIAN EKSTRAK METANOLIK GETAH BIDURI (Calotropis gigantea) TERHADAP KETEBALAN EPITEL GINGIVA TIKUS WISTAR - Meilawaty, Zahara (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
Background: Biduri is a shrub plant sap. The sap extract of this plant can be used to treat inflammation and accelerate wound healing. Objective: Determine the effect of sap extract metanolic biduri of gingival wound healing in wistar rats of thickness epithelium seen histological. Methods: The study used 48 wistar rats. All rat were given injury on their gingival using punch biopsy, further more divided into 4 groups, (1) control (-), given no medication; (2) control (+), given ibuprofen; (3) treatment group, given the extract of sap of biduri 50 mg / kg bw; (4) treatment group, given the extract of sap of biduri 500 mg / kg bw. Furthermore, each of 3 rats in all groups performed decaputation on the on the 2nd, 4th, 8th, and 15th dayâs after injury to take the mandible, after that the histological observation were done. The data were analyzed by two way Anova test, was continued by LSD test. Results: there were significant differences in epithelial thickness in all groups (p<0,05). Conclusion: The methanolic extract of the sap of biduri able to increase the number of rat gingival epithelial thickness so as to accelerate wound healing